Aktivitas Antioksidan dan Kualitas Organoleptik Kombucha Daun Ciplukan pada Variasi Jenis Gula dan Lama Fermentasi - Seyla Dk Rindiani; Titik Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the antioxidant activity of ciplukan leaf kombucha on variations in sugar type and fermentation time and to determine the organoleptic quality of ciplukan leaf kombucha on variations in sugar type and fermentation time. The research method used was descriptive quantitative and qualitative using experimental methods and a Completely Randomized Design with 2 factors with 3 replications. The results of the research showed that the antioxidant activity of ciplukan leaf kombucha was highest in the G1F2 treatment (225 grams of ciplukan leaf kombucha with palm sugar and 7 days of fermentation), namely 47.4%. Meanwhile, the highest organoleptic quality of ciplukan leaf kombucha in the G1F2 treatment (225 gram palm sugar ciplukan leaf kombucha and fermentation time of 7 days) was that it had a pleasant taste, sour taste, had a typical kombucha aroma and was brown in color. In conclusion, the type of sugar has no significant effect on the antioxidant activity of ciplukan leaf kombucha and the fermentation time has a significant effect on the antioxidant activity of ciplukan leaf kombucha. Keywords: Antioxidant Activity, Ciplukan Leaves, Fermentation, Kombucha